Learners’ Anxiety, Self-Efficacy, and Personality as Predictors of Learners' Speaking Performance - Nissa Mawarda Rokhman; Moh. Adnan Latief; Nunung Suryati (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study is intended to find out the effective contributions of learners’ anxiety, self-efficacy, and personality to learners’ speaking performance. The result shows that anxiety gives 18.9% contribution, self-efficacy 32.5%, and personality 10.2% to speaking performance. In conclusion, self-efficacy gives the biggest contribution to the speaking performance of second semester’s learners in English university level.Abstrak: Penelitian ini bertujuan untuk mengetahui sumbangan kecemasan siswa, efikasi diri siswa, dan kepribadian siswa terhadap performa siswa dalam berbicara. Hasil penelitian ini menunjukkan bahwa kecemasan berkontribusi sebesar 18.9%, efikasi diri 32.5% dan kepribadian 10.2%. Kesimpulannya, efikasi diri berkontribusi paling banyak terhadap performa siswa dalam berbahasa Inggris pada semester kedua di tingkat universitas.